Smile and its impacts on mood forming and purchase intentions in retail business - Jappy P. Fanggidae; Noldy D. P. Mumu (Enrichment : Journal of Management, 2023)
This study aims to investigate the impact of employee smiles on consumer purchasing interest in shopping centers. Literature in the field of communication shows that facial expressions are a form of non-verbal communication that is very often used and is more trusted by communication partners than verbal communication. In the retail business, business owners always advise their employees to smile in front of customers to get a positive response from customers. We investigate whether a smiling employee can elicit customers' positive (negative) mood, which eventually influences their purchasing intention. To achieve the research objectives, this research used quantitative experimental methods. Theoretical and practical implications of the study are discussed in this paper.